Evaluating Commercial Moisture Probes in Reference Solutions Covering Mineral to Peat Soil Conditions - Dettmann, U. (2020)
Capacitance and time domain reflectometry (TDR) probes are frequently used for measurements of the volumetric soil water content. The measurement concept is based on the correlation between volumetric water content and dielectric permittivity (ε). While considerable effort has been made to accurately measure ε in the typical range of mineral soils (<40), little attention has been paid to the capability of moisture probes to measure high ε (>40), typical for highly porous media like organic soils. We evaluated the capability of two moisture probe types (TRIME‐PICO 64 and GS3) to measure ε across the range from 1 to 80. In the case of the TRIME probes, different equations to calculate ε from transit times were tested. Measuring in a set of reference solutions, the TRIME probes had an RMSE of 18.73 for ε values derived using the manufacturer's calibration. With a new calibration, the RMSE was decreased to 3.55. The GS3 probes had an RMSE of 3.96. For both probes, uncertainties increased with increasing ε. We also tested the performance for different electrical conductivities of the reference solutions. Accuracy of ε values was unaffected by increasing conductivities for the TRIME probes but decreased for the GS3 probes. The GS3 probes, however, were able to determine electric conductivities accurately, while TRIME probes failed for electrical conductivity although indicated differently by the manufacturer.